(Un)public space: the Lebanese Baher as a liminal arena for wider societal contestations - Kheir Eddine, T (2023)
This thesis primarily deals with the production of (un)public space within the context of the Lebanese baher. Baher (بحر) is an Arabic term that specifically denotes the sea, but also colloquially refers to the coast, the beach, and the public maritime domain. I deploy the prefix (un) in conjunction with ‘public’ in order to convey how spatial articulations of power relations render the baher – along with its users – ‘betwixt and between’ (Turner, 1969) public/private designations, legal/illegal implications, and inclusionary/exclusionary practices. In seeking to understand the production of the baher, I examine the processes, outcomes, and subsequent effects of this socio-spatial production. By forging a dialogue between the theory of the ‘production of space’ (Lefebvre, 1991) and ‘liminality’ as a concept (van Gennep, 1960), I explore the baher as a social space in perpetual (re)production, with its socio-temporal and spatial transformations (Thomassen, 2015) being informed by an interplay of its ‘perceived’, ‘conceived’, and ‘lived’ elements. I engage with the baherscape, or rather landscape of the baher, as an arena for power-related contestations, a site of both oppression and resistance, where different stakeholders meet, negotiate their various interests, and attempt to pursue their respective agendas. In doing so, I ask: How is the baher (re)produced? Who is (re)producing it, for whom, and for what purpose(s)? What can the (re)production of the baher tell us about prevailing constellations of power in Lebanon? In order to address these questions, I deploy a collective case study approach via a triangulation of mixed qualitative methods, with particular emphasis on interviews, (auto)ethnography, and discourse analysis of secondary data. This is achieved across three interconnected empirical chapters, each focusing on a key dimension of (re)production: first, the Lebanese government, with its associated baher governance; second, private beach actors (i.e. administrators and beachgoers), with their identity inspired exclusionary policies and practices; third, civil society groups calling for the ‘right to the baher’. I leverage the ‘baherscape’ as a connecting thread that weaves together empirical chapters, and co-produces this research’s understanding of the production of the baher as an (un)public space. I conclude that baher contestations comprise thresholds that: (re)draw the boundary between public/private, legal/illegal, and inclusion/exclusion; (re)shape a space’s liminal potential as either a conduit for communitas or a platform for othering; and ultimately (re)define urban dwellers’ relationship with the city. Public spaces – like the baher – and their users are thus in dynamic transformation, perpetually (re)produced by and subsequently (re)reproducing society, with resulting processes and configurations denoting shifting ideological articulations of what ‘public space’ is, and which ‘public(s)’ it caters to.